Malaysia Economic Monitor, December 2015 : Immigrant Labour - World Bank Group (World Bank, Washington, DC, 2016)
Growth moderated throughout 2015, affected by a slowdown in private consumption and weak export growth. The authorities have generally managed the downturn in commodity prices and the financial market volatility with a reasonable mix of macro policies. Heightened external volatility calls for prudent macro policies and acceleration of structural reforms. The eleventh Malaysia plan stresses the importance of effective migration management to achieve high-income country status by 2020. Immigration continues to play a crucial role in Malaysia’s development. While job growth has recently been concentrated in high-skilled occupations, three quarters of all jobs in Malaysia are still low- and mid-skilled. Econometric modelling suggests that immigrant workers can raise gross domestic product (GDP) and create employment for Malaysians. The current process for sourcing immigrant workers is complex and costly for the migrant. The immigration system can better meet the country’s development objectives if it is aligned with Malaysia’s human resource development strategy. Global experience shows that successful immigration systems recognize the long-term role of immigrant workers in the hosting country’s economic and social objectives if they are: (a) market-driven, with immigration flows aligned with labor market demands; (b) comprehensive, acknowledging the need for immigrants of all types; and (c) balanced, minimizing the negative impacts on Malaysian workers, and protecting immigrant workers from abuse.